Paclitaxel-induced pneumonitis in patients with breast cancer: case series and review of the literature. (4th March 2017) - Bielopolski, Dana; Evron, Ella; Moreh-Rahav, Osnat; Landes, Michal; Stemmer, Salomon M.; Salamon, Francis
Abstract : Doxorubicin plus cyclophosphamide followed by paclitaxel is a common adjuvant treatment for high-risk breast cancer. It has been associated with pulmonary toxicity in several case reports. We describe three patients in whom interstitial pneumonitis developed immediately after the first paclitaxel exposure and worsened clinically over time. All reported dyspnoea, fever and progressive respiratory distress. Imaging revealed diffuse bilateral pulmonary infiltrates. Other causes of respiratory failure were excluded with laboratory work-up, imaging, biopsy studies and results of antibiotic treatment. The respiratory decline was reversed only after administration of high-dose steroids, an empirical treatment previously reported to be beneficial in similar cases. Although chemotherapy using concomitant or sequential drugs may make identification of the toxic agent difficult, we noted a clear temporal relationship between exposure to paclitaxel and the development of pulmonary toxicity. Furthermore, according to the available literature, it is less likely that a respiratory decline would be caused by either cyclophosphamide or trastuzumab. In conclusion, clinicians should be aware of the potentially life-threatening risk of pulmonary toxicity following paclitaxel treatment. If paclitaxel is halted early and the patient has good lung reserve, pulmonary toxicity can be reversed with high-dose steroid administration.